Praktik Penyembelihan dan Pengolahan Ayam Rumah Potong Ayam Desa Kajen Kabupaten Pekalongan - Muttaqo, Lutfi; Aziz, Abdul; Izza, Siti Zuhrotul (el hisbah Journal of Islamic Economic Law, 2021)
The importance of halal food for Muslims, therefore paying full attention to food from animal sources that will be consumed is important. Especially in the process of slaughtering and processing it. The slaughter of chickens in a chicken slaughter house is in accordance with Islamic Syari’ah because it has fulfilled the pillars and conditions for slaughtering.The method used in this research is field research. The data sources used are primary data and secondary data. Throught a qualitative approach by means of a deduktive method. Then from these facts are analyzed according to related theories and consclusion can be drawn.”Based on the analysis that has been done, it can be concluded that the practice of slaughtering chickens is appropriate. However, for the aplication of Halal certification to the relevant institutions, to obtain certification to guarantee the halalness of chicken meat products must be completed first in accordance with the act.”